War zone refugia? Establishing a baseline for protected waterbirds in a wildlife refuge flanked by agriculture and militarization - Parsons, Michael H. (BMC Res Notes, 2018)
OBJECTIVES: The welfare of threatened fauna should not be assumed merely because their refuges have been designated with protected status. This is particularly true in geographical areas where social/military events drive an under-reported, but potentially lethal, type of human–wildlife interaction. Waterbirds of Gharana Wetland Conservation Reserve consist mostly of threatened species. However, as occurs globally, ‘protected’ fauna near contested borders are sometimes affected by military forces. As part of a larger project to document regional avifauna, we report the seasonal status of waterbirds in order to help establish a baseline for comparing conservation of wildlife within contested areas to that of fauna in more secure refuges. We examined 24 avifauna surveys for relationships between seasons, temperature, individuals and species. RESULTS: 28 of 61 waterbird species were rare. We found seasonal variations in individuals (F(3,731) = 3.82; P < 0.01) and species (F(3,11) = 5.81; P < 0.05) with a major influx in late winter, rather than autumn. Thus, while this sanctuary serves as an over-wintering site, it is also a stop-over site for high-altitude migrations. While providing this baseline, we offer a reminder that the welfare of wildlife in protected areas should be monitored seasonally, with the ongoing threats to their conservation, carefully documented.